Effect of nitrogen and phosphorus fertilization along with foliar spray of calcium chloride and potassium nitrate on performance of cowpea (Vigna unguiculata) + baby corn (Zea mays) intercropping systems - ANJU BIJARNIA; J.P. TETARWAL; BALDEV RAM; ARJUN LAL BIJARNIA; RAJESH KUMAR; ROSHAN KUMAWAT; MONIKA CHOUDHARY (Indian Journal of Agronomy, 2001)
An field experiment was carried out during 2019 and 2020 at Agriculture Research Station, Ummedganj, Kota, Rajasthan, to study the effect of NP fertilization and foliar spray of stress-mitigating chemicals on yield attributes and yields of cowpea [Vigna unguiculata (L.) Walp.] and baby corn (Zea mays L.) in cowpea and baby corn crop- ping system. The experiment was laid out in split split-plot design with 5 intercropping systems, viz. sole cowpea, sole baby corn, cowpea + baby corn (2 : 1), cowpea + baby corn (3 : 1) and cowpea + baby corn (4 : 1) in main plot, 3 fertility levels (100, 125 and 150% recommended dose of fertilizer) in subplot and 2 stress-mitigating chemi- cals (0.5% CaCl and 1% KNO at flowering and pod development stages) in sub-subplot and replicated 4 times. 2 3 Data revealed that, 2 : 1 row ratio of cowpea and baby corn significantly increased the yield attributes of cowpea as well as baby corn over all the remaining row ratios and sole crops. Yields of both crops were significantly higher under their sole cropping and yield decreased significantly in intercropping due to reduction in plant population. In the subplot, all yield attributes and yields of both crops were higher with the fertility level of 150% over lower levels (100% and 125%). The yield attributes and yields of both crops were significantly higher with the foliar spray of 0.5% of CaCl over 1% KNO . 2 3
Keywords: Cowpea + baby corn intercropping system; Fertilization; Foliar spray; RDF; Quality; Yield